If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x+1)-12=4x-84
We move all terms to the left:
4(2x+1)-12-(4x-84)=0
We multiply parentheses
8x-(4x-84)+4-12=0
We get rid of parentheses
8x-4x+84+4-12=0
We add all the numbers together, and all the variables
4x+76=0
We move all terms containing x to the left, all other terms to the right
4x=-76
x=-76/4
x=-19
| 7x/9=20 | | 5/3+2/7w=6/21 | | 8(3-x)=7(x+6) | | 8b-3÷2b+5=-19 | | 8(3-x)=7(x+9) | | 8(3-x)=7(x+9)) | | (5x-4)=(4+10x) | | 0.6=8t+5t2 | | x=117+1/3 | | x+(14x/100)=52000 | | 48/40=x/10 | | 4x+80=1x+432 | | 30/45=2/x | | Y*y+10y-124=0 | | x+x/5+x/4=580 | | 2(b−12)−-5=13 | | 13.77=1.08(c+4)+4.05 | | 9w−-8w+-5=12 | | 19s+18=20s | | 9=-2(j−20)+1 | | 20c+13=-19+18c | | 4+8d=12d | | 2c+8c−5=15 | | -2x+2x-16=-16 | | 1/z+3+5/z+4=1/z^2+7z+12 | | 4x^2-3x=9/2 | | 45/18=v/12 | | 3d−d−2=14 | | 2(k+4)−12=2 | | -3x+7x-5=4(x-1)-11 | | 22-s/3=s | | (4^(x+2)-4^(x+1)=96 |